(untitled) (Perner’s Contacts, 2017)
The aim of the paper is to introduce a decision-making tool for assignment of trains to platforms. Train platforming problem is formulated as special case of parallel machine scheduling problem in which jobs and parallel machines are synonymous with trains and tracks. Objectives of the model are to minimize total delay of trains and to maximize number of trains (station capacity) and to maximize number of connecting trains assigned to the same platform.